Application of Wine and Olive Oil Production Residues as Substrates for the Cultivation of Chrysanthemum morifolium Potted Plants - Toumazou, Georgios; Prasad, Munoo; Chrysargyris, Antonios (My University, 2025)
Peat is widely used as a soilless growing medium due to its favorable physicochemical properties. However, its extraction has a significant environmental impact, highlighting the need for sustainable alternatives. Repurposing residues from olive oil (OR) and wine (GR) production offers a potential solution to reduce peat dependency and promote agricultural circularity. This study investigated the effects of incorporating different ratios of OR and GR (0, 5, 10, 20, and 40% v/v) into peat-based substrates for the cultivation of chrysanthemum (Chrysanthemum morifolium cv. Pina Colada). The addition of OR and GR altered the physicochemical properties of the substrate mixtures. All mixtures maintained electrical conductivity below the maximum threshold for container media (≤0.5 mS cm-1). While GR increased pH, it remained within suitable ranges at 5-10% incorporation. Adding OR decreased total porosity, while GR addition at ≥20% increased it. OR-amended substrates were associated with reduced plant growth, flower production, chlorophyll fluorescence, and relative chlorophyll content, with these effects intensifying at higher OR levels. These outcomes, combined with increased total phenolics, flavonoids, antioxidant activity, and antioxidant enzyme activities, suggest a high stress response, as indicated by increased malondialdehyde and hydrogen peroxide levels. In contrast, GR at ≤ 20% did not induce oxidative stress or negatively affect growth, physiological, or nutritional indices, making it a viable component of peat-based substrate mixtures. The suboptimal performance of OR highlights the need for improved valorization through composting, optimized application rates, and combination with other substrates or residues to enhance its suitability as a horticultural substrate component.
Keywords: grape-mill wastes; olive-mill wastes; ornamentals; peat alternatives; soilless cultivation